Progress of rehabilitation of large housing estates in Katowice (Poland) - Warchalska-TrollAgata (Hungarian Geographical Bulletin, 2013)
Large housing estates (LHEs) built during the communist era in the countries behind the ‘Iron Curtain’, nowadays, are places of residence for 20–30% of their population, covering a considerable amount of space in many cities. Therefore, changes that LHEs are undergoing are crucial for the quality of life of millions of people in Central and Eastern Europe. The aim of this study is to present the recent rehabilitation progress of LHEs through the example of three case study estates from Katowice – the historical centre of the Upper Silesian industrial agglomeration in Poland. Through inventory, mapping and observation, a set of data on the technical and visual state as well as on the functional aspects of the estates in question were gathered. The analysis led to the conclusion, that the general state of the investigated LHEs is satisfactory, but there are considerable differences in the speed of the rehabilitation process, which may result in a deepening polarisation of the quality of life on the estates in the near future.